2007
DOI: 10.1016/j.cplett.2007.02.064
|View full text |Cite
|
Sign up to set email alerts
|

Possible EIT-like effects in strong-field photo-dissociation of carbon disulphide

Abstract: CS 2 molecules are spatially aligned upon irradiation by intense (1-100 TW cm −2 ), 35 ps pulses of 512 nm or 355 nm light. When both colours are simultaneously present, spatial alignment disappears. We draw analogy with weak-field illumination of an atom by two colours wherein EIT (electromagnetically induced transparency) inhibits absorption by virtue of dipoles not being induced in two-colour fields. In the strong field scenario, molecular alignment is a consequence of a dipole being induced in the directio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2007
2007
2008
2008

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…However, the reported anisotropy is by no means an unambiguous proof of the molecular alignment by the laser electric field and can alternatively be interpreted as a sign of the well-known geometric alignment mechanism, which, in fact, refers to the dependence of the ionization probability on the angle between the electric field and the molecular axis . Different ways of disentangling the actual reorientation of the molecular axis toward the laser electric field (often referred to as dynamic alignment) from the geometric alignment effect have been proposed, for instance, the dependence of the angular distributions characteristics (fwhm, ratio of its maximum value to the minimum one) on the laser intensity and the comparison of the ionic signal recorded with linearly and circularly polarized laser fields . These methods are used in single-laser experiments where the same laser pulse is used for the molecular alignment and for the dissociative ionization of the molecular sample.…”
Section: Introductionmentioning
confidence: 99%
“…However, the reported anisotropy is by no means an unambiguous proof of the molecular alignment by the laser electric field and can alternatively be interpreted as a sign of the well-known geometric alignment mechanism, which, in fact, refers to the dependence of the ionization probability on the angle between the electric field and the molecular axis . Different ways of disentangling the actual reorientation of the molecular axis toward the laser electric field (often referred to as dynamic alignment) from the geometric alignment effect have been proposed, for instance, the dependence of the angular distributions characteristics (fwhm, ratio of its maximum value to the minimum one) on the laser intensity and the comparison of the ionic signal recorded with linearly and circularly polarized laser fields . These methods are used in single-laser experiments where the same laser pulse is used for the molecular alignment and for the dissociative ionization of the molecular sample.…”
Section: Introductionmentioning
confidence: 99%
“…Irradiation of these species by such strong optical fields inevitably leads to ionization; the dynamics are highly nonlinear and theoretical treatments have to be nonperturbative. There has been burgeoning interest in strong field molecular dynamics in the course of the past decade or so but the focus of experimental attention has mainly been directed toward studying the positively charged ions that are produced in the course of the field−molecule interaction. We report here the results of a careful experimental study of energy spectra of electrons that are ejected when a series of linear alcohol molecules in the gas phase, methanol, ethanol, and 1-propanol, are ionized using 100−150 fs-long pulses of intense light of either 800 or 400 nm wavelength.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a very recent study in which resonant phenomena has been shown to play a possible role in strongfield ionization dynamics. 37 Strong nonresonant laser fields are known to cause spatial alignment of linear molecules along the optical field polarization direction. However, suppression of this effect has recently been achieved 37 by simultaneous application of two strong fields at two different colors, each of which, when applied individually, gives rise to spatial alignment of the molecule that is irradiated.…”
Section: Introductionmentioning
confidence: 99%
“…There has been a very recent study in which resonant phenomena has been shown to play a possible role in strong-field ionization dynamics . Strong nonresonant laser fields are known to cause spatial alignment of linear molecules along the optical field polarization direction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation